Evolution of a Legal System - Palmer, Sir Geoffrey (Victoria University of Wellington Law Review, 2000)
Notes for a dialogue between Sir Ivor Richardson and the Rt Hon Sir Geoffrey Palmer held at the Australasian Law Teachers’ Association Conference at Victoria University of Wellington, 6 July 1999.